Exploring the impact of targeted overhand serve practice intervention: An approach to improve volleyball players' overhand serving skills - Mardila, Ade Vina; Victorian, Ahmad Richard; Destriana; Destriani (Journal Sport Area, 2024)
Background Problems: The precision of serves in volleyball plays a crucial role in shaping the outcome of a match, potentially altering the game's dynamics, scoring points, and elevating the overall team performance. Research Objectives: This study was conducted to assess the impact of targeted overhand serve drill exercises on overhand serve accuracy. Methods: This study employed a quasi-experimental approach, utilizing a one-group pretest-posttest design, with 30 volleyball extracurricular participants engaging in targeted overhand service drill exercises over 6 weeks. Data were collected using the AAHPER overhand serve accuracy test, followed by analysis through a paired-sample t-test to assess the effectiveness of the training and determine if there were any differences in outcomes between the two groups, with a significance level set at 5%. Before conducting parametric tests, data normality is examined using the Shapiro-Wilk test, and homogeneity is assessed using Levene's test. Findings and Results: In summary, the finding of this study showed that targeted overhand serve drill exercises have a positive effect on enhancing the accuracy of overhand serves in volleyball extracurricular participants. Conclusion: In addition, this intervention can be a valuable training method and reference for designing training programs aims at improving overhand serve accuracy in volleyball matches. Future research should implement stricter controls throughout the experimental process.